2007
DOI: 10.1080/08958370600985859
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Associated with Indoor Air Pollution and Sick Building Syndrome-Related Symptoms among Office Workers in Taiwan

Abstract: This study investigated whether sick building syndrome (SBS) complaints and indoor air pollution for office workers are associated with oxidative stress indicated by urinary 8-hydroxydeoxyguanosine (8-OHdG). With informed consent, 389 employees in 87 government offices of 8 high-rise buildings in Taipei city completed self-reported questionnaires on SBS complaints at work in the past month. Urinary 8-OHdG was determined for each study participant and on-site air pollutants were measured for each office in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Field studies have demonstrated associations between ocular and nasal physiological response and the indoor environment [15]. Oxidative stress has been in focus as an important mechanism behind health effects of outdoor air pollution, but it has recently been shown that oxidative stress can be important for SBS in relation to indoor chemical indoor exposure [16 ].…”
Section: Physiological Methods In Epidemiological Studiesmentioning
confidence: 99%
“…Field studies have demonstrated associations between ocular and nasal physiological response and the indoor environment [15]. Oxidative stress has been in focus as an important mechanism behind health effects of outdoor air pollution, but it has recently been shown that oxidative stress can be important for SBS in relation to indoor chemical indoor exposure [16 ].…”
Section: Physiological Methods In Epidemiological Studiesmentioning
confidence: 99%
“…The accumulation of indoor CO 2 , HCHO, TVOCs, O 3 , PM 10 , bacteria and fungal contamination significantly increases the risks of sick building syndrome (SBS) [6,7,8,9,10,11], and high urinary 8-hydroxydeoxyguanosine (8-OHdG) levels [12,13,14]. Urinary 8-OHdG is considered as a biomarker for oxidative stress and has been significantly associated with building-related complaints in office workers [14,15], the exposure to polyaromatic hydrocarbons in traffic conductors and Chinese military cooks [16,17] as well as the exposure of PM 10 and PM 2.5 in bus drivers [18]. In addition, HCHO may cause nasal and eye irritation, neurological effects, and increased risk of asthma or allergies, and is genotoxic, causing DNA adduct formation and clastogenic effects [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 8-OHdG can be adopted as an effect marker for exposure to pollution. Furthermore, urinary 8-OHdG is associated with both indoor pollutant exposure and self-reported SBS [16], [17]. Although these studies suggest that 8-OHdG is a potential marker for reporting SBS, the etiology of SBS has yet to be fully understood, and a comprehensive approach for examining SBS is not available.…”
Section: Introductionmentioning
confidence: 99%